2008
DOI: 10.1159/000118945
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Poststroke Mortality

Abstract: Background: Obesity is an established cardiovascular risk factor. We studied the association between body mass index (BMI) and all-cause mortality after stroke. Methods: A registry started in 2001 with the aim to register all hospitalized stroke patients in Denmark now includes 21,884 patients in whom BMI was recorded. There are five BMI groups: underweight (BMI <18.5), normal weight (BMI 18.5–24.9), overweight (BMI 25.0–29.9), obese (BMI 30.0–34.9) and severely obese (BMI ≧35). All patients underwent an evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
114
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(125 citation statements)
references
References 43 publications
7
114
1
3
Order By: Relevance
“…25 In our study, we found that overweight/ obese patients also had lower risk of a severe stroke and poststroke pneumonia. These findings add further support to the obesity paradox hypothesis and are in accordance with some 8,10,23 but not all previous studies. 24 A higher BMI has also been associated with a better outcome in several other chronic diseases, and the mechanisms underlying the phenomenon have been debated for years.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…25 In our study, we found that overweight/ obese patients also had lower risk of a severe stroke and poststroke pneumonia. These findings add further support to the obesity paradox hypothesis and are in accordance with some 8,10,23 but not all previous studies. 24 A higher BMI has also been associated with a better outcome in several other chronic diseases, and the mechanisms underlying the phenomenon have been debated for years.…”
Section: Discussionsupporting
confidence: 93%
“…8,10,[22][23][24] However, recently, the obesity paradox was challenged by a study focusing on cause-specific rather than all-cause mortality and reporting no indication of an obesity paradox among stroke patients, when focusing on strokespecific deaths. 25 In our study, we found that overweight/ obese patients also had lower risk of a severe stroke and poststroke pneumonia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For long‐term mortality, with median follow‐up time ranging from 2.5 to 10 years, BMI 25 to 30 was associated with the best survival in many studies. Our results differ from other reports in that we did not find lower mortality with higher BMI beyond mild obesity 6, 7, 18, 19, 20. One reason may be that BMI data are frequently missing in studies of hospitalized patients, where weight is measured at the time of admission.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the reports on how obesity affects stroke in humans are contradictory, as not all studies report a relationship between obesity and increased mortality/morbidity after stroke and some studies suggest that being obese actually leads to a better outcome (Vemmos et al 2011;Ryu et al 2011;Olsen et al 2008;Towfighi and Ovbiagele 2009). The reasons for this 'obesity paradox' are not understood fully but are likely to be due to a complex relationship between how obesity is measured, age, type and severity of stroke and concurrent medication (Katsnelson and Rundek 2011;Towfighi and Ovbiagele 2009).…”
Section: Obesity/metabolic Syndromementioning
confidence: 99%